2015
DOI: 10.1103/physrevb.92.094505
|View full text |Cite
|
Sign up to set email alerts
|

Cesium vacancy ordering in phase-separatedCsxFe2ySe2

Abstract: By simultaneously displaying magnetism and superconductivity in a single phase, the iron based superconductors provide a model system for the study of magnetism's role in superconductivity.The class of intercalated iron selenide superconductors is unique amongst these in having the additional property of phase separation and coexistence of two distinct phases -one majority phase with iron vacancy ordering and strong antiferromagnetism and the other a poorly understood minority microscopic phase with a conteste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…This is in accord with reports on Rb 2 Cr 3 As 3 and Cs 2 Cr 3 As 3 as well as pressure studies both of which found the a-axis more sensitive to external or chemical pressure 4,5,30,31 . These values of α are similar to the relatively high values reported for paramagnetic (PM) states of the 11 and various 122 members of the FBS family where strong spin-fluctuations are thought to contribute to the thermal expansion [32][33][34][35][36][37][38][39] . As we will show similar spin-fluctuations exist in K 2 Cr 3 As 3 and may be responsible for the large α values.…”
supporting
confidence: 85%
“…This is in accord with reports on Rb 2 Cr 3 As 3 and Cs 2 Cr 3 As 3 as well as pressure studies both of which found the a-axis more sensitive to external or chemical pressure 4,5,30,31 . These values of α are similar to the relatively high values reported for paramagnetic (PM) states of the 11 and various 122 members of the FBS family where strong spin-fluctuations are thought to contribute to the thermal expansion [32][33][34][35][36][37][38][39] . As we will show similar spin-fluctuations exist in K 2 Cr 3 As 3 and may be responsible for the large α values.…”
supporting
confidence: 85%
“…Recently, similar behavior was observed in the related intercalated iron selenide '122' family of superconductors (A x Fe 1−y Se 2 with A = Na, K, Rb, or Cs) where it was suggested that the strength and ordering temperature of the magnetic phase was dependent on the size of the intercalating ion and consequently the spacing between the tetrahedral Fe 2 Se 2 layers. 29 For the hole-doped iron arsenide systems being considered here a similar dependence is seen where T N decreases with increasing ionic radius (r A ) as monitored by the a lattice parameter, with T N = 205, 140K and a = 3.9243(1), 3.9625(1)Å for A = Sr and Ba respectively. sition in the iron selenides is not strongly coupled to a structural transition, the strong magneto-elastic coupling in the hole-doped 122 iron arsenides, where magnetism is the primary order parameter, suggests it is likely that the smaller lattice of the Sr system allows for larger magnetic interactions between neighboring iron sites and so enhances the behavior of the structural and magnetic phase transitions.…”
supporting
confidence: 55%
“…The onset of nematic order results in the differentiation of lattice spacings along the Fe-Fe bond directions, characterized by an orthorhombicity [δ = (a−b)/(a+b)] of a few tenths of a percent. In the magnetically ordered state, spins are antiferromagnetically aligned along the longer axis and ferromagnetically aligned along the shorter axis [5,6].Although a multitude of different magnetic orders have been uncovered in related materials [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], observations of intertwined stripe-type magnetic order and nematic order are so far limited to iron pnictides such as LaFeAsO and BaFe 2 As 2 [2, 5, 6]. Upon doping, these intertwined orders are suppressed, giving way to superconductivity near the corresponding quantum critical points [24], evidencing their intimate roles in iron-based superconductivity.…”
mentioning
confidence: 99%